Synthesis of new multitope tetrazole-containing ligands - Grigoriev, Evgeny Y.; Ivashkevich, Ludmila S.; Lyakhov, Alexander S.; Grigorieva, Inna M.; Grigoriev, Yuri V.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2022)
Drawing the experience of 5-phenyl- and 5-pyridyltetrazoles, it was shown that classical nitration-reduction methods in combination with typical alkylation reactions of tetrazole derivatives can be used to obtain multitopic polynuclear tetrazole-containing ligands. Methods for the preparation of a number of previously undescribed polynuclear tetrazole derivatives, including those combining both tetrazole and pyridine rings in the molecule, have been developed. The composition and structure of the obtained compounds were determined by elemental analysis, single crystal X-ray diffraction, NMR and IR spectroscopy. For (5-(pyridin-2-yl)tetrazol-2-yl)(5-(pyridin-2-yl)tetrazol-1-yl)methane the crystalline structure was determined and it was found that this compound forms a 3D polymer framework due to non-classical hydrogen bonds. In its crystal structure there is a network of π – π stacking interactions between tetrazole rings of neighbouring molecules, as well as between pyridine rings.